PENGARUH METODE EKSPERIMEN, MOTIVASI DAN KEAKTIFAN BELAJAR TERHADAP HASIL BELAJAR PADA POKOK GERAK LURUS PADA SISWA SMA NEGERI I AIMAS KABUPATEN SORONG - Kayaman, . (Magister Pendidikan IPA, UNCEN, 2015)
This reseach aims to : Experimental methods to determine the effect on student learning outcomes , To determine the effect motivation on learning outcomes of student learning. ,Study to determine the effect of activity on student learning outcomes.The method used in this research is to use multiple regression correlation, which involved go students of class X SMA Negeri 1 Aimas Sorong Regency Instructional in 2013/2014. The data that was obtained in the form of : Questionnaire experimentation, learning motivation and learning activeness in the experimental class and the control class. Pretest and post-test values in the experimental class and the control class, to determine the effect of experimental methods, motivation, and the activity of learning to student learning outcomes, which if bay using statistical. Conclusions that can be derived from this reseach are experimental method to significantly affect student Learning outcomes to student of SMA Negeri 1 Aimas Sorong Regency. This conclusion is based on test result-calculated F (52.531) > F â table (4.20) Method of learning motivation on Learning outcomes of students a significant effect on students of SMA Negeri 1 Aimas Sorong Regency. Calculated F (47.021) > F â Table (4.20). Learing activenss method students learning outcomes significantly influence to students learning outcomes SMA Negeri 1 Aimas Sorong Regency. This conclusion is based on test results-calculated F (51.311) > F â table (4.20). Keywords: The Effect the experimental methods, The learning motivation and activeness learning on students learning outcomes.